Giải hệ phương trình:

a) \( \left\{\begin{matrix} x - 3y = 11  \\ 2x+y = 1   \end{matrix}\right. \)

b) \( \left\{\begin{matrix} 3x-2y = 7  \\  5x-3y =3  \end{matrix}\right. \)

c) \( \left\{\begin{matrix} x+2y =1  \\   2x +y =2  \end{matrix}\right. \)

d) \( \left\{\begin{matrix} \cfrac{ 4}{x } + \cfrac{3 }{y } = 5 \\  \cfrac{ 1}{x } - \cfrac{ 1}{y } =4  \end{matrix}\right. \)

Giải các hệ phương trình sau bằng phương pháp thế:

a) \( \left\{\begin{matrix}  x - y = 7\\  3x+4y =12  \end{matrix}\right. \)

b) \( \left\{\begin{matrix} x -2y =4  \\  2x+3y = -\cfrac{1 }{ 2}   \end{matrix}\right. \)

c) \( \left\{\begin{matrix} 2x+3y =15  \\  3x - 4y = 9  \end{matrix}\right. \)

Giải các hệ phương trình sau bằng phương pháp cộng đại số:

a) \( \left\{\begin{matrix}  5x-2y =11\\  3x+2y = 3  \end{matrix}\right. \)

b) \( \left\{\begin{matrix} 3x-4y = 5 \\   3x+y -5  \end{matrix}\right. \)

c) \( \left\{\begin{matrix}  x + 2y =5\\  3x +4y =5  \end{matrix}\right. \)

Giải các hệ phương trình sau:

a) \( \left\{\begin{matrix}  \cfrac{ 1}{x-3 } - \cfrac{3 }{y+1 } = 8 \\  \cfrac{ 4}{x -3 }  + \cfrac{1 }{y+1 }= 12   \end{matrix}\right. \)

b) \( \left\{\begin{matrix} \cfrac{6 }{ 2x-1} - \cfrac{4 }{x+y } = -1  \\  \cfrac{ 1}{ 2x-1} -\cfrac{5 }{ x+y} = 0   \end{matrix}\right. \)

c) \( \left\{\begin{matrix} \cfrac{ 1}{x-1 } + \cfrac{1 }{y+1 } = 2  \\   \cfrac{ 2}{ x-1 } - \cfrac{3 }{y+1 } = 1  \end{matrix}\right. \)

Giải hệ phương trình:

\( \left\{\begin{matrix} 3x +2y = 1   \\   5x + 3y = -4 \end{matrix}\right. \)

ĐS: \( \left\{\begin{matrix}  x = -11 \\ y = 17    \end{matrix}\right. \)

Giải hệ phương trình:

\( \left\{\begin{matrix} \cfrac{3 }{x } - \cfrac{4 }{ y} = 2  \\  \cfrac{ 4}{ x} - \cfrac{5 }{y } = 3   \end{matrix}\right. \)

ĐS: \( \left\{\begin{matrix}  x = \cfrac{1 }{2 }  \\ y = 1    \end{matrix}\right. \)

Giải hệ phương trình:

\( \left\{\begin{matrix}  3x - |y | = 1 \\   5x + 3y = 11  \end{matrix}\right. \)

ĐS: \( \left\{\begin{matrix}  x = 1 \\ y = 2    \end{matrix}\right. \)

Giải hệ phương trình:

\( \left\{\begin{matrix}   3 \sqrt{x} - 2 \sqrt{y} = - 1 \\    2 \sqrt{x } + \sqrt{y} = 4 \end{matrix}\right. \)

ĐS: \( \left\{\begin{matrix}  x = 1 \\ y = 4    \end{matrix}\right. \)

Giải hệ phương trình:

\( \left\{\begin{matrix}  x + y = 4023 \\   x - y = 1  \end{matrix}\right. \)

\( \left\{\begin{matrix}  x = 2012 \\   y = 2011 \end{matrix}\right. \)